TECHNOLOGIES FOR ASSESSING THE COMPANY'S INNOVATION POTENTIAL INDEX - Bondarenko, T.G; Borodin, A.I (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article studies contemporary national and international problems of financial maintenance of innovative development of companies. Presents solutions to the identified problems which are the starting point in formulating the main principles of financial support policy of innovative development of oil and gas companies at the national and international levels. An analysis of the current investment projects future investment plans of enterprises and exports have shown that their presence is required in the process of assessing the forecast position of the company. This hypothesis is proved by results of rating estimation of activity of oil and gas companies, calculated according to the model the level of innovation activities. The authors described and illustrated the attempt to predict the possible future positions of the company, by analysing the future perspective, international and regional energy projects. This was analyzed investment projects of the company, forming its investment program and investment flows, and on the basis of their visualized its potential export capacity in 2020. A generalized index of investment potential of oil and gas companies passed the procedure of comparison with the results of the forecast calculations officially published information. To determine the long-term forecast price targets were calculated under different scenarios of development of the cash flow from the export of resources that gave the opportunity to determine the values of the index "retained earnings" for the three scenarios (base, optimistic, pessimistic).